Continuous Professional Development and Teachers Improved Pedagogical Skills in Secondary Schools in Gulu City - Okumu, John Bismarck; Opio, George (East African Journal of Education Studies, 2023)
eachers require improved pedagogical skills and quality for teaching in schools. Continuous Professional Development (CPD) training allows teachers to think more deeply about issues that might come up in the classroom and how they can be resolved. CPD ensures all school staff have the knowledge and skills to support students and help them with their day-to-day roles. Dedicating time to CPD is vital to ensure every staff member learns and grows within their role. The objective of the study is to determine whether Continuous Professional Development improve teachers’ Pedagogical skills in teaching. The study used a cross-sectional survey design. Both qualitative and quantitative research paradigms were used to collect and present data from 14 schools. 14 Headteachers, 14 Deputy Headteachers, 14 Directors of Studies and (336) Teachers were targeted. Data was analysed using Statistical Package for Social Sciences (SPSS) version 18.0 for both inferential and descriptive statistics. The findings revealed that 90% of the teachers agreed that Continuous Professional Development is a teacher training approach that aims at improving teachers’ pedagogical skills in secondary schools. The study concludes that continuous professional development is a vehicle for administrators’ and teachers’ improvement; it helps teachers enhance and acquire new ideas and skills and build confidence and competencies in teaching in secondary schools. It is recommended that CPD requires some restructuring of teachers’ work in schools to support new learning opportunities. School administrators need to develop policies and practices that provide necessary resources such as time, facilities, tools, and incentives